Influence of thermoplastic polyurethane and synthesized polyurethane additive in performance of asphalt pavements. (30th March 2018) - Bazmara, Behrokh; Tahersima, Mohammad; Behravan, Amir
Highlights: Performance of TPU and PU was investigated. Five tests were conducted to evaluate the performance of modified asphalt. Synthesized polyurethane leads to higher asphalt viscosity and stiffness. Modifiers cause better asphalt performance and thermal cracking resistance. Abstract: One of the main concerns in road and transportation engineering is asphalt distress and the immense amount of money spent on repair and maintenance of asphalt pavements. There have been a lot of efforts on improving the bitumen properties to increase the pavement service life span. The modified bitumen with polymers have been used extensively during last decade. In this research, the thermoplastic polyurethane and synthesized polyurethane were employed as the modifier additives in bitumen specimens. The penetration grade, softening point, rolling thin film oven, pressure age vessel, dynamic shear rheometer, bending beam rheometer and fourier transformation infrared spectroscopy tests have been conducted on the modified specimens. The test results indicate that polyurethane causes a lower penetration grade, greater softening point. In addition, polyurethane improved the base bitumen performance in high temperature condition including the higher rutting resistance and the performance grade. Polyurethane has no notable effects on the bitumen performance in low temperature conditions to increase the performance grade. FTIR test results specified the urethane bonds in the modified bitumen which confirms the bond formation in the chemical structure of the binder.